2009
DOI: 10.1007/s10295-009-0574-3
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of Direct Red 28 by mixed bacterial culture in an up-flow immobilized bioreactor

Abstract: Aerobic mixed bacterial culture comprised of five isolates (Bacillus vallismortis, B. pumilus, B. cereus, B. subtilis and B. megaterium) identified by 16srDNA analysis was developed from wastewater samples from the aeration tank of an effluent treatment plant of a textile and dyeing industry and evaluated for its ability to decolorize azo dye Direct Red 28 in an up-flow immobilized packed bed bioreactor using marble chips as support matrix. The bioreactor was operated under two parameters: an aeration rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Toxic effect was probably due to inhibition of cellular metabolic activities and cell growth. Several authors have also reported decreasing color removal with increasing dye concentration during decolorization of other dyes by bacteria [22, 36, 37]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic effect was probably due to inhibition of cellular metabolic activities and cell growth. Several authors have also reported decreasing color removal with increasing dye concentration during decolorization of other dyes by bacteria [22, 36, 37]. …”
Section: Resultsmentioning
confidence: 99%
“…However, due to operational ease and facile adaptability of microorganisms to a given set of conditions, the biodegradation mechanism is considered efficacious in comparison to biosorption for treatment of dye wastewater [21]. Over the past few decades, numerous microorganisms have been isolated and characterized for degradation of various synthetic dyes, but most of the reports have dealt mainly with decolorization of azo dyes [22–24]. There is a dearth of information regarding the degradation and detoxification of triarylmethane dyes by microbial systems despite their increased use by the textile industry.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the inhibition of cell growth and cellular metabolic properties causes toxicity. According to findings from studies on other bacteria and dyes, the decolorization is decreased with the increasing of dye concentration (Jadhav, Jadhav, Kagalkar, & Govindwar, ; Saratale, Saratale, Chang, & Govindwar, ; Tony, Goyal, & Khanna, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to operational ease and facile adaptability of microorganisms to a given set of conditions, the biodegradation mechanism is considered efficacious in comparison to biosorption for treatment of dye wastewater [Singh & Arora., 2011]. Over the past few decades, numerous microorganisms have been isolated and characterized for degradation of various synthetic dyes, but most of the reports have dealt mainly with decolorization of azo dyes [Tony et al, 2009, Gou et al, 2009, Telke et al, 2008. In the present study, a consortium was selected from four consortiums isolated from soil and water samples collected from areas of textile dyeing and printing in Ankleshwar, Gujarat, India and its ability to degrade Reactive Orange M2R (ROM2R) a monoazo dye was analyzed.…”
Section: Introductionmentioning
confidence: 99%